Reinforcement of Biodegradable Sago Starch/Natural Rubber Latex (B-SSNRL) composites by Ultrafine Calcium Carbonate - M.M, Afiq; A.R, Azura (2011)
Natural filler such as sago starch had been widely study as one of the abundantly natural and cheap biomaterials as replacement of conventionally un-degraded plastics or rubber products